Pengaruh Produktifitas Tenaga Kerja Terhadap Keunggulan Komporatif di Era Globalisasi - Purba, Ahmad Fauzan; Tanjung , Dava Maulana; Feryanda Feryanda; Sinaga , Mu’arya; Barus , Muhammad Arif; Sakuntala , Dwita (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
In an era of globalization full of challenges, labor productivity is the main key for Indonesia to achieve comparative advantage in the international market. This research explores the relationship between productivity and competitiveness, focusing on the processing industry subsector that shows extraordinary potential thanks to technological innovation and efficient human resource management. Using a quantitative approach and literature review methods, this research utilizes secondary data from various credible sources, including books and journals, to analyze data characteristics and relationships between variables. Despite progress, Indonesia is still trapped in a productivity gap compared to neighboring countries, which demands strategic steps to improve the quality of education and workforce training. Through collaboration between the government, private sector and educational institutions, it is hoped that an ecosystem will be created that supports improving skills and adopting technology. This research not only provides an overview of the challenges faced, but also offers concrete solutions to prepare Indonesia to face increasingly fierce global competition. By increasing productivity, Indonesia can transform from being just a country with natural resource-based advantages to becoming an innovative force that is highly competitive on the world stage.